(untitled) (Journal of Rangpur Medical College, 2023)
Background: Pressure sores are an ancient medical problem; were even found in autopsies of Egyptian mummies. Sacral pressure sore is more common among paraplegic and bedridden patients. The principle of treatment is excision of all dead & devitalized tissue including scars, underlying bursa, and the involved bone, followed by durable coverage with Flap. Various flaps have been used to reconstruct the pressure sore, including Fasciocutaneous flaps, muscle flaps and free flaps. Among various local flaps, perforators based V-Y advancement fasciocutaneous flap is a reasonable and flexible option with good outcomes for sacral pressure sores reconstruction. Objectives: The purpose of this study was to evaluate the outcome of perforator based V-Y advancement fasciocutaneous flap for sacral pressure sores reconstruction concerning the sociodemographic characteristics of the patients, defect size, and outcome of surgery. Methods: This was a prospective observational study, conducted in the Burn & Plastic Surgery department of Rangpur Medical College Hospital, Rangpur over a period of three years from August 2018 to September 2021 through purposive sampling. Patients of all ages and sexes having grade IV sacral pressure sores were included in this study. In all cases, perforator- based V-Y advancement fasciocutaneous flaps were used. Surgical technique, patient demographics, and outcome were evaluated. Results: A total of 30 patients were operated on. The age range was 18 – 65 years, among them 43.33% of patients were in the age range of 31 – 40 years. 80% of patients in this series were male. Traumatic paraplegia was the main cause of sacral pressure sore, and it was 70%. This study showed that in context to the length and breadth of the wound, a majority (30%) of the patients had a wound dimension of 71–90cm2. The smallest wound dimension was (5x6) = 30cm2 and largest wound dimension was (10x16) = 160cm2. Twenty-one sores that ranged from 6cm to 10cm were reconstructed with unilateral flaps and 09 sores that ranged from 11cm to 16cm were reconstructed with bilateral flaps. In this study, 06 (20%) patients had complications and all were managed conservatively. Three patients had infections and were treated according to the culture sensitivity report. Two patients had marginal flap necrosis at the vertical limb of Y which healed conservatively. One patient developed a seroma due to a blockage of the drain tube, which was resolved spontaneously. There was no flap loss in our study. The average follow-up period was one year. No recurrence of pressure sore during this period. Conclusion: The simplicity of the surgical procedure, minimum or no morbidity in the donor area, and satisfactory outcome in terms of recurrence make this a reasonable option for the reconstruction of the sacral pressure sore. J Rang Med Col. September 2023; Vol. 8, No. 2: 20-24